The Rise of Virulence and Antibiotic Resistance in Staphylococcus aureus - Enany, Shymaa; Crotty Alexander, Laura E. (IntechOpen, 2017)
Staphylococcus aureus (S. aureus) is a growing issue both within hospitals and community because of its virulence determinants and the continuing emergence of new strains resistant to antimicrobiotics. In this book, we present the state of the art of S. aureus virulence mechanisms and antibiotic-resistance profiles, providing an unprecedented and comprehensive collection of up-to-date research about the evolution, dissemination, and mechanisms of different staphylococcal antimicrobial resistance patterns alongside bacterial virulence determinants and their impact in the medical field. We include several review chapters to allow readers to better understand the mechanisms of methicillin resistance, glycopeptide resistance, and horizontal gene transfer and the effects of alterations in S. aureus membranes and cell walls on drug resistance. In addition, we include chapters dedicated to unveiling S. aureus pathogenicity with the most current research available on S. aureus exfoliative toxins, enterotoxins, surface proteins, biofilm, and defensive responses of S. aureus to antibiotic treatment.